Dudziramutauro - Mashiri, Pedzisai; Warinda, Canaan (Gweru, Zimbabwe : Mambo Press, 1999)
On Shona grammer.
Includes bibliographical references (p. 102-103).
In Shona.
Keywords: Shona language -- Grammar